2019
DOI: 10.1590/1981-6723.31018
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-químicas de sucos integrais elaborados a partir de uvas da espécie Vitis rotundifolia

Abstract: Resumo Objetivou-se com este trabalho avaliar o perfil físico-químico de sucos elaborados com uvas das variedades Vitis rotundifolia Regale, Noble, Summit e Carlos. O trabalho foi realizado na Epagri-Videira/SC, nas safras 2016, 2017 e 2018. O delineamento experimental utilizado foi um fatorial duplo (variedade × safra), de forma inteiramente casualizada e com três repetições. As análises físico-químicas realizadas foram: acidez total (AT), teor de sólidos solúveis (SS), relação SS/AT, pH, açúcares redutores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(25 reference statements)
1
5
0
1
Order By: Relevance
“…The very high acidity and lower sweetness resulted in the imbalance between sweet and acid, culminating in the lowest global impression. Similar results were found by Bender et al (2019) in C30 juices, which showed an imbalance due to greater acidity and low sweetness, reflected in the global appreciation, in both extraction systems. Rizzon et al (2018) explain that a sweetness and acidity equilibrium is fundamental for the juice quality, with the sweet flavor collaborating with the structure, while the acidity participates in the freshness and conservation of the product.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The very high acidity and lower sweetness resulted in the imbalance between sweet and acid, culminating in the lowest global impression. Similar results were found by Bender et al (2019) in C30 juices, which showed an imbalance due to greater acidity and low sweetness, reflected in the global appreciation, in both extraction systems. Rizzon et al (2018) explain that a sweetness and acidity equilibrium is fundamental for the juice quality, with the sweet flavor collaborating with the structure, while the acidity participates in the freshness and conservation of the product.…”
Section: Resultssupporting
confidence: 82%
“…Although the pans are easy to use, have a low cost of implantation and provide good quality juices, this process can lead to an incorporation of exogenous water, due to the condensation of the steam used to extract the juice (Bender, Souza, Caliari, Malgarim, & Camargo, 2019;Bresolin, Gularte, & Manfroi, 2013;Marcon et al, 2016). The percentage of water incorporation in the juices made through the extraction pans varies from 7.56% to 20.7% (Marcon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nos sucos, elas apresentam sabor doce, ácido, adstringente e aroma de fruta cozida. Contudo, os sucos fabricados a partir desse tipo de uva possuem grande potencial nutracêutico, facilitando a sua comercialização (BENDER et al, 2019) Obtida através da fermentação alcoólica da uva fresca e madura ou pelo suco de uva fresco, o vinho tem definição bioquímica devido sua caracterização proveniente da fermentação alcoólica dos açúcares de suco de uva pelas leveduras e pelas bactérias láticas. São substâncias que constituem o vinho: os compostos fenólicos, pectinas, compostos voláteis, aromáticos, vitaminas, sais, anidrido sulfuroso, açúcares, álcoois, sais de ácidos minerais e orgânicos, ácidos orgânicos, gomas e mucilagens, substâncias nitrogenadas e pigmentos (LOCATELLI, 2017).…”
Section: Suco De Uva Integralunclassified
“…Grape juice extraction by steam distillation is an alternative for small growers and makes small farms economically feasible (Costa et al, 2019;Marcon et al, 2013), since the extraction pan needed to produce this juice is relatively cheap and easy-to-use apparatus, and "pan juice" is sold primarily at small farm markets and to consumers living near the producing properties, adding value to the raw material and increasing family income (Canossa et al, 2017;Guerra et al, 2016). However, the steam condensation used to extract the juice may cause exogenous water addition (Bender et al, 2019;Bresolin et al, 2013;Marcon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Adding water to juice poses no health risk to consumers, but the product must be clearly labeled to adhere to legislation (IN nº 14, 2018) (Bender et al, 2019(Bender et al, , 2021Bresolin et al, 2013;Guerra et al, 2016;Marcon et al, 2013Marcon et al, , 2016. Bioactive content and profile are influenced by the juice processing techniques, primarily the time and temperature used (Lambri et al, 2015;Lima et al, 2015;Paranjpe et al, 2012;Toaldo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%